(untitled) (Libellarium: journal for research in the field of information and related sciences, 2009)
The history of school libraries in Dalmatia dates back to the 19th century, when they were established as differentiated and defined subjects within the education system in the Austro-Hungarian monarchy. The important heritage of the reform of primary and secondary schools organized by the Austro-Hungarian authorities was the creation of the library network within the education system. This paper describes the situation in the Dalmatian primary school education prior to the 1869 reform, and the institutional framework for the primary school libraries following the reform. It also conceptualizes the social dimension of their work. We have also shown the social, cultural, and economic framework for the reforms, implementation of laws and regulations that focused on their work, and tried to estimate the cultural situation in Dalmatian villages before and after the reform. We have shown the reform of secondary education and the development of secondary school libraries. The libraries were founded after the adoption of the 1871 Act on Principles of Primary School Education, temporary school and teaching regulation of 1870, and the 1871 Regulations on School Libraries. This is the time when regional teacher libraries were established as a tool for the further education of teachers. We have also described the Regulations for both school and teachers’ libraries. Our hypothesis is that schools, including school libraries, are modernizing institutions. As such, school libraries had a wider range of tasks defined within the modernizing transition of Dalmatia in the late 19th century. The basis for such an approach was the analysis of selected reference texts in periodicals and the literature on the history of school education in Dalmatia. Many papers on the reform of primary schools in Dalmatia have been published, but the organization and activities of school libraries has received little attention. This paper focuses on the institutional frameworks for setting up school libraries in Dalmatia within the education reform implemented by the Austro-Hungarian monarchy in the late 19th century, i.e. with the legal and organizational frameworks and their conceptualization in the context of the social situation of the time.